Usefulness of Dried Blood Spots (DBS) to perform hepatitis C virus genotyping in drug users in Senegal. Issue 3 (9th November 2016) - Ndiaye, O.; Gozlan, J.; Diop‐Ndiaye, H.; Sall, A.S.; Chapelain, S.; Leprêtre, A.; Maynart, M.; Gueye, M.; Lo, G; Thiam, M.; Ba, I.; Lacombe, K.; et al.
Abstract : The aim of this pilot study was to analyze the Hepatitis C Virus (HCV) genotypes circulating in Senegal among Drug User (DUs), using Dried Blood Spots (DBS) as RNA source for molecular assays. Heroin and/or cocaine users (n = 506) were recruited in Dakar from April to July 2011, using a Respondent Driven Sampling (RDS) method. DBS preparation consisted of five drops of whole blood from finger applied to a Whatman paper card. HCV infection was screened by the detection of anti‐HCV antibodies, using a rapid immune‐chromatographic test. HCV RNA was quantified on anti‐HCV positive DBS, using the Abbott RealTime HCV® Genotyping was performed on DBS with detectable viral load with Versant® HCV Genotype 2.0 Assay (LiPA) and Abbott RealTime HCV Genotype II assay®. Among the 506 participants, 120 were tested as positive for anti‐HCV antibodies and their samples were analyzed for HCV RNA viral load and genotype. Out of the 120 DBS tested, HCV RNA was detected on 25 (20.8%). The median viral load was 15, 058 IU/ml (ranging from 710 to 766, 740 IU/ml). All positive DBS were suitable for the genotyping assay, that showed a predominance of genotype 1 (21/25) including 16 genotypes 1a and 5 genotypes 1b. HCV genotype 1 prevails in a DU population in Dakar. DBS could be useful for HCV RNA genotyping, but optimal storage conditions should required avoiding RNA impairment. Acknowledging this limitation, DBS could be a great interest for detecting and genotyping HCV viremic patients. J. Med. Virol. 89:484–488, 2017 . © 2015 Wiley Periodicals, Inc.